A method for solving the degradation of lubricating oil performance caused by carbon smoke pollution by using titanium dioxide and molybdenum disulfide composite

By preventing the antagonism between nanomolybdenum disulfide and soot particles by hydrophilic lipophilic nanotitanium dioxide and molybdenum disulfide composite, the problem of degradation of lubricating oil caused by soot pollution is solved, and the improvement of lubricating performance and sulfur content control is achieved. , simplifies the addition process.

CN116836746BActive Publication Date: 2025-01-14DONGGUAN JINSUO LUBRICATING OIL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310808920.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-14
Estimated Expiration
2043-06-30

AI Technical Summary

Technical Problem

The performance of lubricating oil caused by soot pollution is degraded. In the prior art, the single addition of molybdenum disulfide and soot particles have an antagonistic effect, which is ineffective or harmful, and it is difficult to adjust the ZDDP content to match the nano-molybdenum disulfide dosage and soot pollution.

Method used

The composite of hydrophilic lipophilic nanotitanium dioxide and molybdenum disulfide is used as an additive. By adjusting the mass ratio of titanium dioxide and molybdenum disulfide and the preparation conditions, a nanocomposite is formed and added to the lubricating oil contaminated by soot to prevent the nanometers. The antagonism of molybdenum disulfide and soot particles.

Benefits of technology

It effectively improves the lubricating performance of lubricating oil, avoids the combined addition of ZDDP, is simple to operate and has high efficiency, reduces the increase in sulfur content of molybdenum disulfide in the lubricating oil, and significantly improves the problem of lubricating performance degradation caused by soot pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116836746B_ABST
    Figure CN116836746B_ABST
Patent Text Reader

Abstract

A method for using a titanium dioxide and molybdenum disulfide composite to solve the problem of lubricating oil performance degradation caused by carbon soot pollution belongs to the field of lubricating oil additives. Using hydrophilic and lipophilic nano titanium dioxide, sodium molybdate, thioacetamide, etc. as raw materials, a nanocomposite of titanium dioxide and molybdenum disulfide is synthesized, and the nanocomposite of titanium dioxide and molybdenum disulfide with a mass fraction of no more than 2.0% is added to the lubricating oil contaminated by carbon soot, which can solve the problem of lubricating oil performance degradation caused by carbon soot pollution, and at the same time, the lubricating performance of the lubricating oil can be further improved. The method is simple to operate and highly efficient, and has good application prospects in the fields of molybdenum disulfide lubricants, engine lubricating oil additives, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lubricating oil additives, and specifically relates to a method for solving the degradation of lubricating oil performance caused by carbon smoke pollution by using a titanium dioxide and molybdenum disulfide composite. Background Art

[0002] Engine soot is the product of incomplete combustion of fuel oil. It is composed of carbon, ash and unsaturated (unburned) hydrocarbons. Its main component is carbon (about 90%), and the rest is a small amount of oxygen, hydrogen, nitrogen, sulfur, etc. Most of the soot will be discharged into the atmosphere, causing environmental pollution problems, and the rest of the soot will enter the engine oil to pollute the engine oil, causing the lubricant performance to decline. Solving the problem of engine lubricant performance decline caused by soot pollution is of great practical significance.

[0003] Molybdenum disulfide, especially nano-scale molybdenum disulfide, has excellent lubricating properties and is a potential lubricating additive for engine oil. Adding nano-scale molybdenum disulfide is an effective method to improve the performance of lubricating oil. Preliminary work shows that in lubricating oil contaminated by carbon soot, if molybdenum disulfide is added alone, it will produce an antagonistic effect with carbon soot particles, not only ineffective, but harmful. According to patent CN104974818A, nano-scale molybdenum disulfide with a spherical structure can be used as a compound additive with zinc dialkyl dithiophosphate (ZDDP), which can be dispersed and added to ester lubricating oil contaminated by carbon soot to solve the problem of decreased performance of ester lubricating oil caused by carbon soot. Mechanism research has confirmed that the main reason for the antagonistic effect of nano-molybdenum disulfide and carbon soot particles is that carbon soot particles prevent nano-molybdenum disulfide from forming a film on the friction surface. ZDDP can help nano-molybdenum disulfide form a film, and the synergistic effect of the two can effectively improve the lubrication performance. ZDDP is an indispensable component in engine lubricating oil. For formulated oil, its type and content are limited, and it is difficult to adjust the content according to the amount of nano-molybdenum disulfide used and the amount of carbon soot pollution.

[0004] In order to find a better method, based on the accumulation of previous work, it is planned to replace the scheme of compounding nano molybdenum disulfide and ZDDP by a composite of nano molybdenum disulfide. Obviously, the other component compounded with nano molybdenum disulfide should have the function of removing the inhibition of carbon smoke on the film formation of molybdenum disulfide on the friction surface, and at the same time, it should have a synergistic lubrication effect with molybdenum disulfide. Literature reports that nano titanium dioxide and molybdenum disulfide have a synergistic lubrication effect (CN201010524516.8, Tribology Letters, 2011, 43: 77-87), but it is unknown whether titanium dioxide can remove carbon smoke from nano molybdenum disulfide on the surface. Through the analysis of the surface properties of carbon smoke and nano molybdenum disulfide, the present invention designs a method for solving the lubrication performance degradation caused by carbon smoke pollution by a nano composite of hydrophilic and oleophilic nano titanium dioxide and molybdenum disulfide. Summary of the invention

[0005] In order to overcome the above-mentioned defects in the prior art, the present invention provides a method for solving the degradation of lubricating oil performance caused by carbon soot pollution by using a titanium dioxide and molybdenum disulfide composite, without the need to jointly add nano molybdenum disulfide and ZDDP to inhibit the degradation of lubricating performance of ester lubricating oil caused by carbon soot pollution.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for solving the problem of lubricating oil performance degradation caused by carbon soot pollution by using a titanium dioxide and molybdenum disulfide composite, using a nanocomposite formed by hydrophilic and lipophilic titanium dioxide and molybdenum disulfide as an additive, adding it to the lubricating oil contaminated by carbon soot to solve the problem of lubricating oil performance degradation caused by carbon soot pollution.

[0008] As a preferred technical solution, the nanocomposite is added as an additive to the lubricating oil polluted by carbon soot in an amount of 0.05-2.0%. In the prepared nanocomposite additive, the mass ratio of titanium dioxide to molybdenum disulfide is 1:0.05-20.

[0009] As a preferred technical solution, the method steps for preparing a nano-composite additive are as follows: sodium molybdate and thioacetamide are dissolved in water at a molar ratio of 1:0.1-20, and then hydrophilic and lipophilic titanium dioxide is added, and the mass ratio of titanium dioxide to molybdenum disulfide in the prepared product is maintained at 1:0.05-20 by adjusting the mass of titanium dioxide, and an excess of concentrated hydrochloric acid is added at 50-100°C, and the reaction starts and a precipitate is produced; the precipitate is filtered, washed, dried, and calcined at 400-1000°C for 10-300 minutes under a protective atmosphere to obtain a nano-composite of titanium dioxide and molybdenum disulfide.

[0010] The present invention also proposes a method for preparing a titanium dioxide and molybdenum disulfide composite, wherein sodium molybdate and thioacetamide are dissolved in water at a molar ratio of 1:0.1-20, and then hydrophilic and lipophilic titanium dioxide are added, and the mass ratio of titanium dioxide to molybdenum disulfide in the prepared product is maintained at 1:0.05-20 by adjusting the mass of titanium dioxide, and an excess of concentrated hydrochloric acid is added at 50-100°C, and the reaction starts and precipitation is generated; the precipitate is filtered, washed, dried, and calcined at 400-1000°C for 10-300 minutes under a protective atmosphere to obtain a nano-composite of titanium dioxide and molybdenum disulfide.

[0011] The titanium dioxide and molybdenum disulfide complex prepared by the present invention can be used as an additive to solve the problem of lubricating oil performance degradation caused by carbon smoke pollution. Specifically, the complex is added as an additive to the lubricating oil polluted by carbon smoke, and the addition amount of the complex is 0.05-2.0%.

[0012] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0013] 1. Using hydrophilic and lipophilic nano-titanium dioxide, sodium molybdate, thioacetamide, etc. as raw materials, synthesize a nano-composite of titanium dioxide and molybdenum disulfide, and add the nano-composite of titanium dioxide and molybdenum disulfide with a mass fraction of no more than 2.0% to the lubricating oil contaminated by carbon soot, which can solve the problem of lubricating oil performance degradation caused by carbon soot pollution, and can also further improve the lubricating performance of the lubricating oil. This method is simple to operate and highly efficient, and has good application prospects in the fields of molybdenum disulfide lubricants, engine lubricating oil additives, etc.

[0014] 2. The solution proposed by the present invention can effectively prevent the antagonistic effect between nano-molybdenum disulfide and carbon soot particles, and can be directly used in the modification of lubricating oil contaminated by carbon soot.

[0015] 3. Compared with the combined solution of nano-molybdenum disulfide and ZDDP, the solution proposed by the present invention does not require the addition of ZDDP, has little effect on the inherent composition of the engine's full formula lubricating oil, and is simple to operate and highly efficient.

[0016] 4. After titanium dioxide is introduced into the composite, the total addition ratio remains unchanged, and the actual amount of molybdenum disulfide required is significantly reduced, which can prevent the excessive increase of sulfur content in the lubricating oil caused by the addition of nano molybdenum disulfide. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 TEM image (a) and XRD pattern (b) of the prepared hydrophilic and lipophilic titanium dioxide / molybdenum disulfide nanocomposite.

[0018] As can be seen from the figure, compared with the common titanium dioxide / molybdenum disulfide nanocomposite reported in the literature (Tribology International, 2015, 92: 172-183), the molybdenum disulfide morphology is basically similar, presenting a hollow spherical structure, and the lubrication effect of the two should be comparable. It can be inferred that lipophilic and hydrophilic nano-titanium dioxide plays a key role in solving carbon soot pollution.

[0019] Figure 2 This is a comparison chart of the results of using the hydrophilic and lipophilic titanium dioxide and molybdenum disulfide nanocomposite to solve the lubrication antagonism between nano molybdenum disulfide and carbon smoke particles.

[0020] from Figure 2It can be seen that after replacing nano-molybdenum disulfide with hydrophilic-lipophilic titanium dioxide and molybdenum disulfide nanocomposite, there is no need to add ZDDP. Compared with the lubricating oil contaminated by carbon soot, the lubrication performance is significantly improved, indicating that hydrophilic-lipophilic titanium dioxide can effectively prevent the antagonistic effect between nano-molybdenum disulfide and carbon soot particles, thereby solving the problem of decreased lubrication performance caused by carbon soot pollution.

[0021] Figure 3 It is a comparison of the effects of the complex formed by hydrophilic and lipophilic titanium dioxide and ordinary nano titanium dioxide in solving carbon smoke pollution.

[0022] As can be seen from the figure, when the mass fraction of soot pollution is 1%, the friction coefficient of the lubricant modified by the complex formed by hydrophilic and lipophilic titanium dioxide and ordinary nano-titanium dioxide is basically the same, but the wear rate is significantly different. The wear rate of the former is about 50% smaller than that of the latter, indicating that hydrophilic and lipophilic titanium dioxide can solve the problem of lubricant performance degradation caused by soot pollution to a greater extent after being compounded with nano-molybdenum disulfide. DETAILED DESCRIPTION

[0023] Example 1

[0024] 0.1 mol of sodium molybdate and 0.6 mol of thioacetamide were dissolved in sufficient water, and then hydrophilic and lipophilic titanium dioxide was added. The amount of hydrophilic and lipophilic titanium dioxide added was adjusted to ensure that the mass ratio of titanium dioxide to molybdenum disulfide in the product was 2:1. Excessive concentrated hydrochloric acid was added at 80°C, and the reaction started and precipitated. The precipitate was filtered, washed, dried, and calcined at 500°C for 50 minutes under a protective atmosphere to obtain a nanocomposite of titanium dioxide and molybdenum disulfide. The characterization results are as follows: Figure 1 The above compound was weighed at a mass fraction of 0.5% in the lubricating oil and added to the dioctyl sebacate lubricating oil containing 0.5% soot. The lubrication performance was significantly improved. The results are shown in Figure 2 shown.

[0025] Example 2

[0026] 0.1 mol of sodium molybdate and 0.4 mol of thioacetamide were dissolved in sufficient water, and then hydrophilic and lipophilic titanium dioxide was added. The amount of hydrophilic and lipophilic titanium dioxide added was adjusted to ensure that the mass ratio of titanium dioxide to molybdenum disulfide in the product was 1:4. Excessive concentrated hydrochloric acid was added at 85°C, and the reaction started and precipitated. The precipitate was filtered, washed, dried, and calcined at 600°C for 20 minutes under a protective atmosphere to obtain a nanocomposite of titanium dioxide and molybdenum disulfide, and its characterization results were similar to Figure 1 The above compound was weighed at a mass fraction of 1.5% in the lubricating oil and added to the dioctyl sebacate lubricating oil containing 1.0% soot. The lubrication performance was significantly improved (the improvement effect was similar to Figure 2 shown).

[0027] Example 3

[0028] 0.1 mol of sodium molybdate and 0.8 mol of thioacetamide were dissolved in sufficient water, and then hydrophilic and lipophilic titanium dioxide was added. The amount of hydrophilic and lipophilic titanium dioxide added was adjusted to ensure that the mass ratio of titanium dioxide to molybdenum disulfide in the product was 1:1. Excessive concentrated hydrochloric acid was added at 75°C, and the reaction started and precipitated. The precipitate was filtered, washed, dried, and calcined at 480°C under a protective atmosphere for 60 minutes to obtain a nanocomposite of titanium dioxide and molybdenum disulfide, and its characterization results were similar to Figure 1 The above compound was weighed at a mass fraction of 1.0% in the lubricating oil and added to the dioctyl sebacate lubricating oil containing 0.5% soot. The lubrication performance was significantly improved (the improvement effect was similar to Figure 2 shown).

[0029] Example 4

[0030] 0.2 mol of sodium molybdate and 0.4 mol of thioacetamide were dissolved in sufficient water, and then hydrophilic and lipophilic titanium dioxide was added. The amount of hydrophilic and lipophilic titanium dioxide added was adjusted to ensure that the mass ratio of titanium dioxide to molybdenum disulfide in the product was 6:1. Excessive concentrated hydrochloric acid was added at 82°C, and the reaction started and precipitated. The precipitate was filtered, washed, dried, and calcined at 550°C for 180 minutes under a protective atmosphere to obtain a nanocomposite of titanium dioxide and molybdenum disulfide, and its characterization results were similar to Figure 1 The above compound was weighed at a mass fraction of 0.5% in the lubricating oil and added to the dioctyl sebacate lubricating oil containing 0.5% soot. The lubrication performance was significantly improved (the improvement effect was similar to Figure 2 shown).

[0031] Example 5

[0032] 0.2 mol of sodium molybdate and 0.9 mol of thioacetamide were dissolved in sufficient water, and then hydrophilic and lipophilic titanium dioxide was added. The amount of hydrophilic and lipophilic titanium dioxide added was adjusted to ensure that the mass ratio of titanium dioxide to molybdenum disulfide in the product was 1:1. Excessive concentrated hydrochloric acid was added at 82°C, and the reaction started and precipitated. The precipitate was filtered, washed, dried, and calcined at 480°C under a protective atmosphere for 180 minutes to obtain a nanocomposite of titanium dioxide and molybdenum disulfide, and its characterization results were similar to Figure 1 The above compound was weighed at a mass fraction of 1.8% in the lubricating oil and added to the dioctyl sebacate lubricating oil containing 1.5% soot. The lubrication performance was significantly improved (the improvement effect was similar to Figure 2 shown).

[0033] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for solving the degradation of lubricating oil performance caused by carbon smoke pollution by using a titanium dioxide and molybdenum disulfide composite, characterized in that: The nanocomposite formed by hydrophilic and lipophilic titanium dioxide and molybdenum disulfide is used as an additive and added to the lubricating oil contaminated by carbon soot to solve the problem of lubricating oil performance degradation caused by carbon soot pollution; The preparation method of the nano-composite additive comprises the following steps: dissolving sodium molybdate and thioacetamide in water at a molar ratio of 1:0.1-20, adding hydrophilic and lipophilic titanium dioxide, adjusting the mass of titanium dioxide to maintain the mass ratio of titanium dioxide to molybdenum disulfide in the prepared product at 1:0.05-20, adding an excess of concentrated hydrochloric acid at 50-100°C, reacting and generating precipitation; filtering, washing, drying and calcining the precipitate at 400-1000°C for 10-300 minutes under a protective atmosphere to obtain a nano-composite of titanium dioxide and molybdenum disulfide.

2. The method according to claim 1, characterized in that The nanocomposite is an additive and its mass fraction added to the lubricating oil contaminated by carbon soot is 0.05~2.0%.

Citation Information

Patent Citations

  • Molybdenum disulfide nanosphere / titanium dioxide composite material and preparation method thereof

    CN101979480B

  • Molybdenum disulfide nanosphere / titanium dioxide composite material and preparation method thereof

    CN101979480A

  • Method for inhibiting reduction of lubricating property of ester lubricant due to carbon smoke pollution

    CN104974818A